Expression and secretion of synaptic proteins during stem cell differentiation to cortical neurons. (December 2018) - Nazir, Faisal Hayat; Becker, Bruno; Brinkmalm, Ann; Höglund, Kina; Sandelius, Åsa; Bergström, Petra; Satir, Tugce Munise; Öhrfelt, Annika; Blennow, Kaj; Agholme, Lotta; Zetterberg, Henrik
Abstract: Synaptic function and neurotransmitter release are regulated by specific proteins. Cortical neuronal differentiation of human induced pluripotent stem cells (hiPSC) provides an experimental model to obtain more information about synaptic development and physiology in vitro. In this study, expression and secretion of the synaptic proteins, neurogranin (NRGN), growth-associated protein-43 (GAP-43), synaptosomal-associated protein-25 (SNAP-25) and synaptotagmin-1 (SYT-1) were analyzed during cortical neuronal differentiation. Protein levels were measured in cells, modeling fetal cortical development and in cell-conditioned media which was used as a model of cerebrospinal fluid (CSF), respectively. Human iPSC-derived cortical neurons were maintained over a period of at least 150 days, which encompasses the different stages of neuronal development. The differentiation was divided into the following stages: hiPSC, neuro-progenitors, immature and mature cortical neurons. We show that NRGN was first expressed and secreted by neuro-progenitors while the maximum was reached in mature cortical neurons. GAP-43 was expressed and secreted first by neuro-progenitors and its expression increased markedly in immature cortical neurons. SYT-1 was expressed and secreted already by hiPSC but its expression and secretion peaked in mature neurons. SNAP-25 was first detected in neuro-progenitors and the expression and secretion increased gradually during neuronal stages reaching a maximum in mature neurons. The sensitive analytical techniques used to monitor the secretion of these synaptic proteins during cortical development make these data unique, since the secretion of these synaptic proteins has not been investigated before in such experimental models. The secretory profile of synaptic proteins, together with low release of intracellular content, implies that mature neurons actively secrete these synaptic proteins that previously have been associated with neurodegenerative disorders, including Alzheimer's disease. These data support further studies of human neuronal and synaptic development in vitro, and would potentially shed light on the mechanisms underlying altered concentrations of the proteins in bio-fluids in neurodegenerative diseases. Highlights: Human iPSC-derived cortical neurons express and secrete synaptic proteins. NRGN, GAP-43 and SNAP-25 are first expressed and secreted by neuro-progenitors. SYT-1 is expressed and secreted by stem cells. Synaptic proteins are secreted the highest when mature cortical neurons are formed.